Association Between Initiation of Rehabilitation and Length of Hospital Stay for Workers with Moderate to Severe Work-Related Traumatic Brain Injury - Suk Won Bae; Min-Yong Lee (Safety and Health at Work, 2023)
Background: In workers with moderate to severe work-related traumatic brain injury (wrTBI), this study aimed to investigate the effect of the timing of rehabilitation therapy initiation on the length of hospital stay and the factors that can influence this timing. Methods: We used data obtained from the Republic of Korea's nationwide Workers' Compensation Insurance. In the Republic of Korea, between the years 2010 and 2019, a total of 26,324 workers filed a claim for compensation for moderate to severe wrTBI. Multiple regression modeling was performed to compare the length of hospital stay according to the timing of rehabilitation therapy initiation following wrTBI. According to the timing of the initiation of rehabilitation therapy following TBI, the proportions of healthcare institutions that provided medical care during each admission step were compared. Results: The length of hospital stay for workers who started rehabilitation therapy within 90 days was significantly shorter than that for workers who started rehabilitationment were first admitted to tertiary hospitals. Approximately 39% of patients who received delayed rehabilitation treatment were first admitted to general hospitals, and 28.5% were first admitted to primary hospitals. Conclusions: Our findings demonstrate the importance of early rehabilitation initiation and that the type of healthcare institution that the patient is first admitted to after wrTBI may influence the timing of rehabilitation initiation. The results of this study also emphasize the need to establish a Worker’s Compensation Insurance–specialized rehabilitation healthcare delivery system.